The Importance of Initial Management in Ocular Chemical Burn: A Case Series: Poster Presentation - Case Series - Ophthalmologist - dr. ANDREAS SURYA ANUGRAH, Sp.M; dr. Reny Setyowaty, Sp.M (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ocular chemical injuries are true emergency which requires immediate intervention. Delayed management may result in severe eye injuries. This report aims to describe the effectivity of initial management and medical treatment of ocular chemical burns. Case Illustration : We reported four cases of ocular chemical injuries due to alkaline, acidic, and unspecified chemical compound. All subjects were men, aged 30 to 50 years old. They had injuries at work and none of them used eyewear protector. Each was brought to emergency unit in less than 2 hours. They were given initial timely irrigation until pH neutralized. Ocular damages were evaluated using Roper-Hall Classification, three cases were Roper-Hall 2 and other was Roper-Hall 3. After initial management, all cases were treated with medical treatment and showed significant improvement. After 6 months follow up, there weren’t any long-term sequelae in all subjects. Discussion : Serious eye damage results from strongly alkaline or acidic compounds. Most critical factor is timely delivery of irrigating fluid. Irrigation should ideally be performed with isotonic saline or lactate ringer solution and continued until the pH neutralized to a physiological level. Any method of irrigating the eye is preferable than delay in elimination of the destructive chemical. Medical treatments in acute management of severe ocular chemical burns are anti-inflammatory therapy, halting epithelial and stromal breakdown, promoting re-epithelialization and promoting corneal stromal healing. Conclusion : Timely irrigation of the eye effectively reduces severity of chemical burns, reduces need for surgical intervention, and improves final visual acuity if combined with medical treatment in golden period.